2015
DOI: 10.1155/2015/158061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ondansetron on the Occurrence of Hypotension and on Neonatal Parameters during Spinal Anesthesia for Elective Caesarean Section: A Prospective, Randomized, Controlled, Double-Blind Study

Abstract: To prevent hypotension during spinal anesthesia for caesarean section, we assessed IV ondansetron of invasive maternal hemodynamic and fetal gazometric parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
45
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 18 publications
(30 reference statements)
12
45
1
Order By: Relevance
“…A meta‐analysis by Heesen et al . found less of a decrease in blood pressure among patients treated with 5‐HT 3 antagonists in all included obstetric studies . These findings were confirmed by the current results but seem to be caused by increased administration of sympathomimetics.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A meta‐analysis by Heesen et al . found less of a decrease in blood pressure among patients treated with 5‐HT 3 antagonists in all included obstetric studies . These findings were confirmed by the current results but seem to be caused by increased administration of sympathomimetics.…”
Section: Discussionsupporting
confidence: 87%
“…found no difference among patients needing treatment with sympathomimetics during CD . When investigating the total dose of vasopressors, several studies found decreased requirements for ephedrine or phenylephrine among patients previously treated with 5‐HT 3 antagonists; however, the present study recorded a substantially higher need for sympathomimetics among the granisetron group versus the control group.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…[19] However, it should be noted that different hypotension's management protocols were used. They found that prophylactic ondansetron (4 mg) had a significant effect on the incidence of hypotension in healthy parturient undergoing SA for elective cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…also reported that ondansetron can be helpful to improve metabolic and vital parameters of newborns. [19]…”
Section: Discussionmentioning
confidence: 99%